2007
DOI: 10.1128/aem.02084-06
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Metabolic Responses of Bacillus subtilis to the Availability of Organic Acids: Transcription Regulation Is Important but Not Sufficient To Account for Metabolic Adaptation

Abstract: The soil bacterium Bacillus subtilis can use sugars or organic acids as sources of carbon and energy. These nutrients are metabolized by glycolysis, the pentose phosphate pathway, and the Krebs citric acid cycle. While the response of B. subtilis to the availability of sugars is well understood, much less is known about the changes in metabolism if organic acids feeding into the Krebs cycle are provided. If B. subtilis is supplied with succinate and glutamate in addition to glucose, the cells readjust their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 44 publications
2
57
0
Order By: Relevance
“…With the cdaA promoter, about 40 units of ␤-galactosidase were detected irrespective of the available carbon source. Such an activity is often observed for weak constitutive promoters (34). In contrast, no promoter activity was detectable upstream of the glmM gene (see Table 2).…”
Section: Resultsmentioning
confidence: 88%
“…With the cdaA promoter, about 40 units of ␤-galactosidase were detected irrespective of the available carbon source. Such an activity is often observed for weak constitutive promoters (34). In contrast, no promoter activity was detectable upstream of the glmM gene (see Table 2).…”
Section: Resultsmentioning
confidence: 88%
“…Future lines of study will investigate the involvement of MA secretion on induction of bacterial volatile signaling in B. subtilis, which has been reported to be involved in the induction of ISR in B. subtilis-colonized plants . Concomitantly, others have reported that a few organic acids, especially oxaloacetate, trigger the operon for Bacillus acetoin production alsSD (Schilling et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…6) (42). Until now, catabolite repression of TCA cycle-encoding genes was assumed to be exclusively elicited by glycolytic carbon sources (43).…”
Section: Intracellular Metabolite Concentrations and Reactionmentioning
confidence: 99%